Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project seed distribution for the October-November-December 2023 ‘short rains’ season - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
AICCRA project distributed 20 tons of improved seed varieties (pearl millet, sorghum, green gram, pigeonpea) to 15,030 farmers in Kitui, Makueni, and Taita Taveta Counties, Kenya, during the October-November-December 2023 'short rains' season. Of the total seed recipients, 530 were women farmers from Association of Women in Agriculture AWAK, a local women-led organization, benefitting from a partnership established in early 2023. Coordinated by county extension officers and Trainer of Trainees (ToTs) at each ward, the distribution aimed to enhance agricultural productivity. Improved climate resilient seed varieties were selected based on farmers' preferences and agroecological zones, contributing to improved access to climate-smart agriculture technologies in Kenya's drylands.